In search of a sanctuary: Zimbabwean migrants in South Africa. - Chirongoma, Sophia (Abilene Christian University Press., 2016)
This chapter will explore the struggles that Zimbabwean immigrant encounter in a foreign land, challenge the Zimbabwean churches to address the causes of this current humanitarian crisis, and urge the South African churches to embrace the immigrant community and be involved in works of healing, restoring, nurturing, and caring for life—as reflected in the struggles of the Central Methodist Mission. And the churches of the immigrants themselves need to answer Bernard Boyo’s call in the prior chapter for a theology of: ; immigration—one that urges believers at the point of departure to press for justice, those who receive the refugees to practice radical hospitality, and those who are the church in exile to walk together with those who suffer.